Job displacement insurance: an overview - Parsons, Donald O. (Bonn, 2014)
"Earnings losses from permanent job separations are a serious threat to the financial security of long-tenured workers. Job displacement insurance is presumably designed to offset these losses, but evidence suggests that consumption smoothing among the long-tenured displaced is seriously incomplete, at least in lightly regulated labor markets. Unemployment and reemployment wage insurance could fully cover these losses, but are costly to provide. Severance pay has emerged as a supplemental, if much criticized, instrument. Moral hazard limitations on unemployment insurance generosity mean that severance pay functions as scheduled (partial) unemployment insurance and scheduled wage insurance. Consumption smoothing over time through savings and borrowing is less efficient than ideal insurance, but may be preferred in second-best situations. Long-tenured separated workers are older on average, which introduces special problems, but also additional policy options, including early access to retirement accounts."